Baptizing Management - Poole, Eve (Studies in Christian ethics, 2008)
This paper argues that management practices are more readily portable across the sectors than has often been supposed, while indicating where particular care will be needed in translation. The paper suggests, however, that political pressure for control and an epistemological bias may prove to be management's Achilles heel. Further, it examines some dilemmas in the relationship between the manager and the managed, and queries the professions' outrage at being subject to increasingly overt management.